2020
DOI: 10.18502/kss.v4i14.7886
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship Education and Entrepreneurial Intention among Disability Students in Higher Education

Abstract: Entrepreneurship education helps to form appropriately entrepreneurial mindsets and behaviors in students. This is not only for normal students but also students with special needs in tertiary institutions. This study aims to identify the entrepreneurial intention of students with special needs (disability) at Jakarta State University (UNJ). This research used the case study research method, where the casesare students with disabilities at UNJ who are registered as active students. Data was collected using uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Financially stable families influence EWDs in entrepreneurial decisions due to their early stage of interaction and support system from family (Saxena & Pandya, 2018). Disabled students gain knowledge about entrepreneurship from their immediate social environment such as family namely parents, relatives and college friends who were already entrepreneurs (Maulida et al, 2020).…”
Section: Family Environment (Fe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Financially stable families influence EWDs in entrepreneurial decisions due to their early stage of interaction and support system from family (Saxena & Pandya, 2018). Disabled students gain knowledge about entrepreneurship from their immediate social environment such as family namely parents, relatives and college friends who were already entrepreneurs (Maulida et al, 2020).…”
Section: Family Environment (Fe)mentioning
confidence: 99%
“…Males have more intentions towards entrepreneurship, attitude towards behaviour perceived behaviour control and level of entrepreneurial intention than compared to females. There is no difference in gender in social norms (Ponmani et al, 2014) Female disabled students have shown more interest in entrepreneurship activity than males and prioritize skill expertise whereas male disabled respondents concentrate on capital for running a business (Maulida et al, 2020). Gender has a significant impact on attitudes toward entrepreneurship among Male entrepreneurs.…”
Section: H0 3: Family Support (Fs) Significantly Positively In Entrep...mentioning
confidence: 99%
“…Why is that? Because entrepreneurship education also helps form the right entrepreneurial behavior mindset in students [9].…”
Section: Introductionmentioning
confidence: 99%